Evaluation of People's Satisfaction towards Services of Bangplub Subdistrict Municipality, Pak Kret District, Nonthaburi Province - Punchakhetthikul, Nakamon; Rungrojchaiyaporn, Pusit (Arts of Management Journal, 2024)
The objectives of this research were to study 1) the level of satisfaction of citizens with the services provided by Bangplub Subdistrict Municipality. Pak Kret District, Nonthaburi Province 2) the problems, obstacles, and suggestions towards providing services to the people of Bangplub Subdistrict Municipality; and 3) the guidelines for providing services in Bangplub Subdistrict Municipality. The population used in this research includes people who come to use the services of Bangplub Subdistrict Municipality. The total population is 11,564 people. The sample size used in this research is 400 people, according to population statistics from house registrations separated by area and village. Statistics for data analysis include descriptive statistics, including percentages, means, and standard deviations. The results of the research found that the service recipients were satisfied with the service. Overall satisfaction is at its highest level ( = 4.83). Satisfaction of service recipients with the service according to the opinions of service recipients. Classified according to service channels at the highest level, the total mean is equal to ( = 4.92) the satisfaction of the service recipients with the service. According to the opinions of service recipients categorized by service personnel, satisfaction is at the highest level ( = 4.94) of service recipients with the service. Satisfaction is at the highest level ( = 4.94) of service recipients. Categorized by facilities, satisfaction was at the highest level ( = 4.94) and the satisfaction of the service recipients overview and classification according to the work that service recipients contact to receive services was at the highest level ( = 4.91).